2018
DOI: 10.1186/s12936-018-2536-6
|View full text |Cite
|
Sign up to set email alerts
|

Another challenge in malaria elimination efforts: the increase of malaria among adults after the implementation of long-lasting insecticide-treated nets (LLINs) in Dielmo, Senegal

Abstract: BackgroundThe widespread use of artemisinin-based combination therapy (ACT) and long-lasting insecticide-treated nets (LLINs) has led to an impressive decrease of malaria burden these recent years in Africa. However, some new challenges about the future of malaria control and elimination efforts have appeared. Among these challenges, the loss and—or—the only partial acquisition of anti-Plasmodium immunity among exposed populations lead to an increase of the age at risk of malaria. Indeed, older children and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The mosquito bed net has been demonstrated to be highly effective if it is properly utilized. 81 In contrast, the report of Wotodjo et al 82 in Senegal showed no association between mosquito bed net and malaria infection. The lack of association observed might be due to improper use of mosquito net.…”
Section: Discussionmentioning
confidence: 89%
“…The mosquito bed net has been demonstrated to be highly effective if it is properly utilized. 81 In contrast, the report of Wotodjo et al 82 in Senegal showed no association between mosquito bed net and malaria infection. The lack of association observed might be due to improper use of mosquito net.…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, mosquitoes are more attracted to households with a large family [ 42 ], so family size does need to be considered in the design of ITN distribution campaigns. Higher parasitaemia was observed among those with low ITN use in Tanzania [ 43 ] while malaria incidence in Senegal [ 44 ] rose after the third year when ITN ownership had declined. Therefore, it may be more cost effective to distribute slightly too many nets rather than too few nets to ensure households have enough serviceable ITNs to cover the population, to slow the process of net damage as the protective effect of ITNs declines through time as nets accumulate damage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively similar incidences of both asymptomatic and symptomatic malaria among the age groups suggests that intensive control has shifted the age pattern of the risk of infection away from children compared to before the intervention [ 11 ], as seen elsewhere in Africa [ 28 , 29 ]. This indicates that adults in Malabo have partially lost their acquired immunity, are at increased risk of malaria with or without symptoms, and will need additional protection when they visit areas of high transmission like mainland EG.…”
Section: Discussionmentioning
confidence: 99%